European experience on the practical use of levosimendan in patients with acute heart failure syndromes - Follath, F (2005)
The novel calcium sensitizer and ATP-dependent potassium channel opener levosimendan has been introduced for routine use in several European countries. Recent reports on clinical experience confirm the positive hemodynamic results and beneficial clinical effects described in the initial dose-finding and randomized comparative therapeutic trials in patients with severe low-output heart failure. In addition, studies in small series of patients with cardiogenic shock after myocardial infarction and/or surgical interventions and post-interventional myocardial dysfunction (stunning) indicate that the inotropic and vasodilating actions of levosimendan may be of value in a wider range of indications. Dose recommendations, combination with other drugs, and potential side effects are discussed in this overview.